1 Everyday ethical challenges in specialist palliative care practice in Uganda: a semi-structured interview study. (14th March 2023) - Schofield, Guy; Nakiganda, Harriet; Brangan, Emer; Acuda, Wilson; Huxtable, Richard; Selman, Lucy E
Abstract : Background: Ethical challenges (ECs) arise daily in the delivery of specialist palliative care, but there is limited evidence regarding the range and nature of ECs, with no evidence from Africa. Understanding these ECs is crucial to inform education and training and adequately support staff. Aim: To explore and map the ethical challenges experienced by specialist palliative care practitioners (SPCPs) in clinical practice in Uganda. Methods: Semi-structured interview study conducted with a purposive sample of SPCPs of any professional background practicing across multiple sites in Uganda. Results: 36 interviews were conducted, with 17 nurses, 8 physicians, 5 clinical officers, and 6 social workers, working at 7 sites. 25 different EC areas were identified and grouped across four main thematic areas: inside the consultation (communication, best interest, autonomy and decision making, goals of care); bedside deliberations (challenging stigma, confidentiality, genetics); engaging institutions (policy and guidelines, prioritising institutional resources, working with colleagues); and navigating society (legal issues and human rights, fairness and justice, spirituality and care). The four main themes were impacted by four cross-cutting themes: gender, resources, working with families, and traditional health beliefs. Challenges were described in a highly contextual manner, rather than via ethical principles. Conclusion: This in-depth study demonstrates the huge breadth of ethical challenges faced by Ugandan SPCPs in their day-to-day practice, broader than current curricula. The highly contextual nature in which these challenges were discussed has implications for design and delivery of training materials that support SPCPs in daily practice. No current comparable data exists for the UK or Irish setting and the contextual nature of these results makes a strong argument for this work to be repeated to address this gap.